PERANAN SATUAN POLISI PAMONG PRAJA DALAM MENGIMPLEMENTASIKAN PERATURAN DAERAH TENTANG PEDAGANG KAKI LIMA DI KABUPATEN KUTAI TIMUR - Salasiah Nurhayati (ADMINISTRASI PUBLIK, 2017)
Jobs not only in the formal sector but also in the informal economy. Street vendors (PKL) were employed in the informal sector, therefore street vendors also need to be maintained within improving the under middle class society's economy. In order to improve the economy of street vendors, street vendors need their arrangement to create public order. As municipal police officers are empowered to enforce legislation concerning expected to arrange PKL well, therefore this informal sector workers do not lose their livelihoods that can lead to new unemployment.The problems of this research are: 1) How is the role of municipal police in implementing the regional regulation on street vendors in the East Kutai Regency, 2) What activities are carried out in municipal police in the organization of street vendors in East Kutai, and 3) What constraints experienced by municipal police in the arrangement PKL in East Kutai and how to overcome them. This study used a qualitative approach. This study was conducted in East Kutai. The data source of this research is the municipal police, street vendors in Sangata, street vendors consumers, street vendors and the community rather than consumers. The focus of this study were 1) The role of municipal police in implementing the regulation of street vendors in the East Kutai Regency, 2) activities implemented municipal police in the arrangement of street vendors, and 3) The problem faced in penetaan PKL municipal police in East Kutai. The methods of data collection using the method of observation, interviews, documentation and library research. The validity of the data using a triangulation method. Analysis of data using interactive analysis funsional stemming from data collection, data reduction, data presentation, and conclusion.The results showed that: 1) The role of municipal police in the implementation of the regulation of street vendors was a sweeping and socializing, controlling the activities carried out with a very good, namely the existence; (1) preventive action by conducting dialogue with vendors to define the collective agreement, (2) prosecution and enforcement, (3) repression can say no, and (4) the action after street vendors relocated and 2) The problem faced municipal police in the arrangement street vendors come from the East Kutai Regency; (1) The internal factors such as; lack of personnel and infrastructure to the incompatibility of the amount of regulation that should be implemented municipal police and (2) external factors such as; lack of understanding of the regulation of society, especially street vendors (PKL).